The Secular in South, East, and Southeast Asia - Dean, Kenneth; van der Veer, Peter (Global Diversities, 2019)
This innovative edited collection provides a comprehensive analysis of modern secularism across Asia which contests and expands prevailing accounts that have predominantly focused on the West. Its authors highlight that terms like 'secular', 'secularization', and 'secularism' do not carry the same meanings in the very different historical and cultural contexts of Asia. Critiquing Charles Taylor's account of secularism, this book examines what travelled and what not in 'the imperial encounter' between Western secular modernity and other traditions outside of the West. Throughout the book, state responses to religion at different points in Chinese and South-East Asian history are carefully considered, providing a nuanced and in-depth understanding of post-secular strategies and relations in these areas. Particular attention is given to Catholicism in the Philippines, Vietnam, and Singapore, and Hinduism and Chinese religion in Malaysia, Singapore, and India. This theoretically engaged work will appeal to students and scholars of Asian studies, anthropology, religious studies, history, sociology, and political science.